Supply Chain Management Analysis Using the Business Process Model and Notation in the Midst of Covid-19 Pandemic - Nania Nuzulita; Rheinata Saskya Aziizah Djohan; Salsabila Roiqoh (Journal of Accounting and Strategic Finance, 2020)
Supply Chain Management (SCM) aims to maximize the value of the products produced to meet customers' needs and demands. This study aims to conduct an assessment of Supply Chain Management at MS Company and suggested BPMN with adjusted business processes. The Business Process Model and Notation (BPMN) approach is useful for describing complex business process modelling in detail but still easy to understand. Thus, it can minimize errors in implementing business processes. We used the study case approach to conduct this research by studying several journals related to SCM. A discussion was then held to improve the four main processes associated with SCM, and the improvement was written by using BPMN. This study explains that BPMN can be used to give detail and minimize errors so that the modified business process modelling is easy to understand and facilitates communication between business process designers and business process executors. Some MS company improvement in its SCM includes production scheduling, goods procurement, production implementation, and warehouse management. It is suggested that further observation and examination of the improved SCM is needed to prove the new SCM's success in the midst of the covid-19 pandemic.